Psychological and metabolic features of young people with stage 1 hypertension and disgarmonious fat component - G.P. Siabrenko; I.I. Kyrychenko; A.S. Shklyar; G.A. Tereshchenko; E.O. Prykhodko; A.O. Demikhov (Вісник медичних і біологічних досліджень, 2021)
Prevention of hypertension is a less expensive and much safer process than interventions such as coronary artery bypass grafting and dialysis, which may be required in the absence and detection of asymptomatic hypertension. The problem of identifying young people with hypertension at an early stage, stratification of cardiovascular risk (CVR), individual selection of adequate therapy, as well as the introduction of preventive measures against the most common factors of CVR, including overweight (OW) at the primary care stage help needs further study. The aim of the study – to learn the clinical and metabolic characteristics of young people with stage 1 hypertension and OW. Materials and Methods. The study examined 74 patients aged 18–44 years with a verified diagnosis of hypertension stage I and BMI, who were divided into two clinical groups, depending on the level of SVR (21 patients with low CVR (LCVR), and 53 patients with moderate CVR (MCVR). After signing informed consent of the patient, based on the analysis of complaints, anamnesis, physical and laboratory methods of monitoring, ultrasound examination and determination level of the CVR respondents were divided into two groups. When determining CVR using an online calculator calculated the total CVR at the level of SBP, HDLP and smoking status, as well as the CVR for BMI. Evaluation of blood pressure was performed by measuring SBP and DBP with mechanically device MicrolifeBPAG1-20 (Switzerland). When measuring anthropometric indicators we determined body weight (kg), height (m). Based on these parameters, the body mass index(BMI) and assessed the degree of obesity. Results. Clinical and laboratory examination of young patients with stage 1 hypertension and OW, divided into persons with low cardiovascular (lCVR) and moderate cardiovascular risk (mCVR) found that: – frequency of early cardiovascular diseases among parents of patients (severe heredity); significantly (p <0.001) more often it was registered in the group of patients with moderate CVR than among patients with low CVR (respectively among (98.1±1.9) % and (61.9±10.6) % of patients, p <0.001); – an increase in the level of total cholesterol (CH) in the serum over 5.0 mmol/dm3 was found among (96.2±2.6) % of patients with mCVR and significantly (p <0.001) less often in the group with lCVR – among (61.9±10.6) % of persons;– a decrease in the level of TNF-α less than 95.0 pkg/cm3 was found among (73.6±6.1)% of patients with moderate CVR and significantly (p <0.01) less often in the group with lCVR – among (28.6±9.9) % of people, due to the lower frequency of people with higher CVR. The mathematical functional dependence between the content of TNF-α and BMI is determined and the nomogram of TNF-α estimation depending on CVR is substantiated; – higher levels of leptin content were found among (81.1±5.4) % of patients with mCVR and significantly (p <0.01) less often in the group with low CVR – among (38.1±10.6) % of persons. The mathematical functional dependence between serum leptin content and BMI was determined and the nomogram of BMI – dependent leptin evaluation was substantiated. Conclusions. The increase of CVR in patients with stage I hypertension and OW is associated with a number of risk factors and metabolic characteristics of patients. Analysis of candidate factors for the assessment of CVR revealed that of the 23 clinical-laboratory and anamnestic signs, only 7 of them have reliable (p <0.05) prognostic indicators for the assessment of CVR at a young age in the presence of stage 1 hypertension in combination with OW